2009
DOI: 10.1177/0300985809359054
|View full text |Cite
|
Sign up to set email alerts
|

Brachyspira murdochii Colitis in Pigs

Abstract: The weakly beta-hemolytic porcine spirochete Brachyspira murdochii is considered a normal intestinal commensal. In the present study, however, a field case of B murdochii-associated catarrhal colitis was identified in a pig, as characterized by extensive spirochetal colonization of the surface epithelium. Experimentally, 8 weaned pigs were challenged with the B murdochii isolate, reproducing catarrhal colitis in 2 animals. By applying fluorescent in situ hybridization using a species-specific oligonucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
0
21
1
2
Order By: Relevance
“…A more recent study from the U.S. confirmed the predominance of B. murdochii amongst Brachyspiraisolates from pigs with mild to moderate mucoid diarrhoea (Hammer and Gebhart, 2013). Hence B. murdochii generally is the most commonly identified weakly haemolytic species in pigs with diarrhoea, including in Spain and Portugal, and this is important given that there is histopathological and experimental infection data supporting its likely role as a pathogen (Weissenböck et al, 2005;Komarek et al, 2009;Jensen et al, 2010). The significance of the other weakly haemolytic species is less clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study from the U.S. confirmed the predominance of B. murdochii amongst Brachyspiraisolates from pigs with mild to moderate mucoid diarrhoea (Hammer and Gebhart, 2013). Hence B. murdochii generally is the most commonly identified weakly haemolytic species in pigs with diarrhoea, including in Spain and Portugal, and this is important given that there is histopathological and experimental infection data supporting its likely role as a pathogen (Weissenböck et al, 2005;Komarek et al, 2009;Jensen et al, 2010). The significance of the other weakly haemolytic species is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…The three strongly haemolytic species Brachyspira hyodysenteriae, "Brachyspira suanatina" (Råsbäck et al, 2007a) and "Brachyspira hampsonii" (Chander et al, 2012) are porcine pathogens, causing colitis, whilst the weakly haemolytic species vary in their pathogenic potential. Brachyspira pilosicoli is a pathogen, being the agent of porcine intestinal spirochaetosis (Trott et al, 1996), Brachyspira murdochii has been associated with mild colitis and diarrhoea (Weissenböck et al, 2005;Komarek et al, 2009;Jensen et al, 2010;Hammer and Gebhart, 2013), Brachyspira intermedia is of uncertain clinical significance in pigs, and Brachyspira innocens generally has been considered to be non-pathogenic (Hampson, 2012). Recently, pigs colonized with one or more of any of these four weakly haemolytic species were shown to have a 5% increase in colonic thickness, and impairment of the colonic mucosa (Fjelkner et al, 2012) and hence interest is refocusing on weakly haemolytic species as potential pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…A milder enteric syndrome of chronic mucodiarrheal disease of grower-finisher pigs, termed porcine intestinal spirochetosis, is caused by Brachyspira pilosicoli (1). Brachyspira murdochii is commonly isolated from healthy pigs; however, some studies have found it to be associated with mild diarrhea and/or colitis (6,7).…”
mentioning
confidence: 99%
“…Na medicina veterinária, a FISH foi utilizada para diagnosticar vários agentes infecciosos tais como Tritrichomonas foetus (Gookin et al 2010), Lawsonia intracellularis (BoutruP et al, 2010;Jensen et al, 2010a), Pasteurella multocida (Pors et al, 2011a;PORS et al, 2011b), picornavírus (durAnd et al, 2008) (Boye et al, 1998;Jensen et al, 2010b). No trabalho de BoutruP et al (2010), a técnica de FISH foi também utilizada para determinar que a L. intracellularis, frequentemente encontrada no citoplasma de macrófagos na lâmina própria, era viável, indicando que possivelmente possa existir transmissão e proliferação do microorganismo nestas células, além de enterócitos.…”
Section: Aplicaçõesunclassified